MENGOPTIMALKAN EFISIENSI DAN MANAJEMEN MELALUI OVEN OTOMATIS DENGAN TEKNOLOGI EXHAUST FAN - Arizal, Heru; Arifiana, Deny; Ridlwan, Ahmad Ajib; Yunus, Yunus; Saputra, Catur Surya; Prayogo, Aji Catur; Anshari, Bima (Jurnal Abdimas Bina Bangsa, 2024)
"UD. ADON JAYA" is a small business that produces salted eggs. Based on direct observation of partner salted egg processing still using conventional methods that require salted egg production time up to eight days. Original salted egg results with a shorter shelf life, which only lasts for seven days. Boiling salted eggs still has a fairly fishy odor. Many boiled eggs are also cracked and broken due to stacking and high boiling temperatures. Procurement and application of an automatic salted egg oven equipped with an exhaust fan, thermocontroll and timer has a capacity of up to 600 eggs with a process that takes five hours. The implementation of this community empowerment service activity is carried out through several stages, namely discussion, observation, and implementation. The results of good condition egg production using the tool every week have increased, besides that it can also be seen that the average percentage of egg dredging using the tool is 5%. The implementation of this activity solves the problem of production aspects to improve the quality and quantity of salted egg production "UD. ADON JAYA" to have a longer shelf life, free of fishy odor, no cracked or broken eggs to meet market demand and solve the problem of weak production management and financial management of partner businesses.